Optimized CNT-PDMS Flexible Composite for Attachable Health-Care Device - Jian Du; Li Wang; Yanbin Shi; Feng Zhang; Shiheng Hu; Pengbo Liu; Anqing Li; Jun Chen (Sensors, 2020)
The CNT-PDMS composite has been widely adopted in flexible devices due to its high elasticity, piezoresistivity, and biocompatibility. In a wide range of applications, CNT-PDMS composite sensors were used for resistive strain measurement. Accordingly, the percolation threshold 2%~4% of the CNT weight ratio in the CNT-PDMS composite was commonly selected, which is expected to achieve the optimized piezoresistive sensitivity. However, the linear range around the percolation threshold weight ratio (2%~4%) limits its application in a stable output of large strain (>20%). Therefore, comprehensive understanding of the electromechanical, mechanical, and electrical properties for the CNT-PDMS composite with different CNT weight ratios was expected. In this paper, a systematic study was conducted on the piezoresistivity, Young’s modulus, conductivity, impedance, and the cross-section morphology of different CNT weight ratios (1 to 10 wt%) of the CNT-PDMS composite material. It was experimentally observed that the piezo-resistive sensitivity of CNT-PDMS negatively correlated with the increase in the CNT weight ratio. However, the electrical conductivity, Young’s modulus, tensile strength, and the linear range of piezoresistive response of the CNT-PDMS composite positively correlated with the increase in CNT weight ratio. Furthermore, the mechanism of these phenomena was analyzed through the cross-section morphology of the CNT-PDMS composite material by using SEM imaging. From this analysis, a guideline was proposed for large strain (40%) measurement applications (e.g., motion monitoring of the human body of the finger, arm, foot, etc.), the CNT weight ratio 8 wt% was suggested to achieve the best piezoresistive sensitivity in the linear range.